Constraints on the delivery of animal-source foods to infants and young children : Case studies from five countries - Pachón, Helena; Simondon, KB; Fall, ST; Menon, Purnima; Ruel, Marie T.; Hotz, C; Creed-Kanashiro, Hilary M.; Arce, B.; Liria Domínguez, M.R.; Frongillo, Edward A.; Brown, D.L. (SAGE Publications, 2007)
Background. Optimal feeding of infants and young children in developing countries includes daily feeding of animal-source foods.